2010
DOI: 10.1182/blood-2010-01-265611
|View full text |Cite
|
Sign up to set email alerts
|

ATP confers tumorigenic properties to dendritic cells by inducing amphiregulin secretion

Abstract: IntroductionThe interactions between the immune system and angiogenesis are determinant for the regulation of tumor growth. The mechanisms of these interactions are not well understood at this time. Dendritic cells (DCs) are known to play a central role in these interactions by releasing vascular endothelial growth factor-A (VEGF-A). 1,2 VEGF-A is able to induce endothelial-like differentiation of tumor-infiltrating precursors of DCs and their migration to vessels to participate to vasculogenesis. 3 VEGF-A was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…Amphiregulin also elevates angiogenic activity, promoting tumor growth and metastasis in pancreatic, colorectal, liver, and lung cancers (9)(10)(11)(12). A recent study has indicated that cancer-derived ATP increased the expression of amphiregulin in DCs in a mouse lung cancer cell line (13). Patients with high levels of amphiregulin have poorer prognoses and higher resistance than patients with low levels of amphiregulin (14).…”
mentioning
confidence: 99%
“…Amphiregulin also elevates angiogenic activity, promoting tumor growth and metastasis in pancreatic, colorectal, liver, and lung cancers (9)(10)(11)(12). A recent study has indicated that cancer-derived ATP increased the expression of amphiregulin in DCs in a mouse lung cancer cell line (13). Patients with high levels of amphiregulin have poorer prognoses and higher resistance than patients with low levels of amphiregulin (14).…”
mentioning
confidence: 99%
“…UTP also induced amphiregulin shedding from LPS-stimulated murine bone marrow-derived, but not from human monocyte-derived, dendritic cells [78]. Moreover, suramin inhibited ATPγS-induced amphiregulin shedding from human monocyte-derived dendritic cells [78], but the specific P2 receptors involved were not identified.…”
Section: Amphiregulinmentioning
confidence: 90%
“…UTP also induced amphiregulin shedding from LPS-stimulated murine bone marrow-derived, but not from human monocyte-derived, dendritic cells [78]. Moreover, suramin inhibited ATPγS-induced amphiregulin shedding from human monocyte-derived dendritic cells [78], but the specific P2 receptors involved were not identified. Notably, amphiregulin released from murine bone marrow-derived dendritic cells stimulated tumour growth in vivo [78] indicating that nucleotides can confer tumourigenic properties to dendritic cells by inducing amphiregulin release.…”
Section: Amphiregulinmentioning
confidence: 90%
See 2 more Smart Citations